The development of outcome key performance indicators for systemic anti-cancer therapy using a modified Delphi method - O'Donovan, Anita; Hayes, Catherine (My University, 2020)
Objective: Performance measurement of health services informs safe, quality care. Key performance indicators (KPIs) offer one such measurement. Limited research exists on outcome KPIs in systemic anti‐cancer therapy (SACT). The objective of this study was to develop outcome KPIs for SACT services. Methods: A Delphi panel of patient advocates and health professionals (n = 35) rated KPIs over four rounds. Participants rated KPIs on validity, reliability, acceptability and feasibility and addressed barriers and facilitators to implementation. Qualitative and quantitative data analyses included Kendall's coefficient of concordance, Wilcoxon signed‐rank test on stability of responses and Kruskal–Wallis test for differences in stakeholder groups' responses. Results: Twenty‐six KPIs reached agreement, of which nine were prioritised. These were a mixture of outcome and process measures: death within 30 days of SACT, neutropenic sepsis, assessment of palliative care needs, medication errors, multidisciplinary team discussion, patient information and timeframe from surgery to SACT. There was weak agreement on the prioritised list (Kendall's coefficient, p = .012). There was good stability of responses between rounds and no difference between responses of stakeholder sub‐groups (p ≥ .05). Conclusion: The study provides a comprehensive identification of outcome measures for SACT which will be useful in developing a framework for the performance measurement of SACT services.
PUBLISHED
Keywords: Cancer; Delphi; KPIs; Outcome; SACT